Contribuições para o ensino das atividades circenses na educação física escolar: um olhar para a formação continuada - Andrade, Maiara Rosa Souza (Universidade Federal de São Carlos, 2025)
The integration of circus activities into school Physical Education expands pedagogical possibilities, fostering students' motor, social, and cultural development. However, its implementation still faces challenges, particularly in the final years of Elementary School and in High School, due to gaps in teacher training and the absence of more objective guidelines in school curricula. Given this scenario, this research investigates the challenges faced by Physical Education teachers in effectively integrating circus activities into their classes and examines whether and how these teachers seek continuing education in this area. The study aims to understand these challenges among teachers in the state public school system of Itaquaquecetuba-SP, proposing ways to strengthen this pedagogical practice. To achieve this, specific objectives were defined, such as highlighting the relevance of circus activities in school Physical Education, examining their presence in official documents, and exploring the relationship between teacher training and this theme. The research adopted a qualitative methodology, using a semi-structured questionnaire applied online, through social media, to state school teachers working in the final years of Elementary School and in High School. The analyzed data indicate that, although circus activities are included in the Currículo Paulista and the BNCC (Base Nacional Comum Curricular), their approach is superficial, making practical application difficult. Furthermore, it was found that initial training in Physical Education rarely includes circus teaching in a consistent manner, and the continuing education offered by the São Paulo State Department of Education (SEDUC-SP), through EFAPE and ATPC/APCF, is predominantly theoretical, lacking practical experiences that equip teachers with the necessary tools. As a result, circus practices remain limited in schools, restricting their educational potential. Given this scenario, this research aims to contribute to the improvement of teacher training by encouraging the creation of more practical courses and the development of specific pedagogical materials. In this way, the study seeks to strengthen school Physical Education, making it more diverse, inclusive, and connected to the cultural richness of the circus, promoting new forms of learning and expression for students.
Contributions to the teaching of circus activities in school physical education: a look at continuing educatio
Keywords: Atividades circenses; Formação continuada; Educação física escolar; CIENCIAS DA SAUDE::EDUCACAO FISICA